Potentional radiosensitizer effect of TUDCA in a obesity model of brain tumor cells - Silva, Liliana (2022)
Obesity may play an important role in the biology of seve ral types of cancer, but the correlation with glioma Is still not very well defined. Former studies indicated that obesity may be related with an decreased resistance to radiation and increased redox status in brain tumors. Since radiothetapy is the most commonly treatment modality used in this type of tumor, we creale a new model of experiments to determinate the influence of obesity in glioma cells [n the presence of radiation with an imbalance of redox status, BC3H1 glioma cells were treated with t-BOOH (150~M), TUDCA (25~M) and a mix of t-BOOH and TUOCA{150~M and 25~M respectively) in serum-free OMEM or conditioned media (CM) from differentiated 3T3-L 1 adj pocytes. Afterwards the cells were irradiated with a total dose of 2 Gy. Subsequently BC3H1 viability was evaluated, by MTT assay, after 4 and 12 hours. We observed an increase in viability In all cells treated solely with 3T3-L 1 eM. Interestingly, in the presence of CM plus TUDCA or t-BOOH, the viability of 6C3H1 was inferior of TUOCA or t~BOOH treatments alone, this effect was independent of irradia tion. After 12 hours the I/iability of the glioma cells was significantly higher on irradiated ceUs treated only with eM, this effect was not yet observed at the 4 hours time point But, in the presence of mix of t~BOOH and TUDCA, with eM and irradiation the cells viability decrea se significanUy. The 3T3-L 1 Me increase (he cell viabrlity in the presence of radiation or not, after 12 hours expose" But in the presence of oxidatIve inducer and, In specially, with the antioxidant TUDCA, the BC3Hi viability significantly decrease. So, we observed a potential radiosensitfzer effect of TUDCA in BC3H1 in the presence of 3T3-L1 adipocytes.